Pengaruh dari promosi serta penjualan personal terhadap putusan pembelian pada konsumen terhadap bahan bangunan cv. Putra mas pratama medan - Sofyan, Silvia; Robin, Robin (JEBIM Prima, 2023)
With the help of data gathering techniques like collecting questionnaires, this study sought to understand the degree to which promotion and personal selling have an impact on consumer purchasing decisions for construction material items at CV Putra Mas Pratama. Before gathering information for more in-depth research, the validity and reliability of this questionnaire will be evaluated. The traditional assumption test and multiple linear regression analysis were used as the analysis techniques in this study. The findings of this study will later demonstrate that the influence of promotions and sales can have a favorable and considerable impact on consumers' decisions to buy particular products. This is evident and will be later demonstrated by the tcount results, which are 3.961 > from ttable, which are 1.660, and a meaningful number that is less than 0.1, or 0.000. Although personal selling only little and significantly influences purchasing choices. tcount, which is 3.838 > from ttable, which is 1.660, and a significant value below 0.1, which is 0.000, might later be used to further support this claim. Sales promotion and personal selling combined will be able to influence purchasing decisions favorably and significantly. Fcount, which is 25.430> from Ftable 2.36, and a substantial value below 0.1, which is 0.000, can both support this claim. 34.6% of the influence is given, while the remaining percentage may be influenced by factors unrelated to this study.